Revisiting SARS-CoV-2 environmental contamination by patients with COVID-19: The Omicron variant does not differ from previous strains. (May 2022) - Glinert, Itai; Ben-Shmuel, Amir; Szwartcwort-Cohen, Moran; Beth-din, Adi; Laskar, Orly; Barlev-Gross, Moria; Melamed, Sharon; Arbell, Noga; Levy, Haim; Horowitz, Netanel A; Weiss, Shay
HIGHLIGHTS: Inferred viral shedding (cycle threshold [Ct] values) was not different between first variants and Omicron. No viable SARS-CoV-2 virus was detected in air samples taken in proximity to patients. No viable SARS-CoV-2 virus was detected in surface samples taken near patients. Omicron-enhanced transmissibility was not a result of acquiring airborne infectivity. Abstract: SARS-CoV-2 Omicron strain emergence raised concerns that its enhanced infectivity is partly due to altered spread/contamination modalities. We therefore sampled high-contact surfaces and air in close proximity to patients who were verified as infected with the Omicron strain, using identical protocols applied to sample patients positive to the original or Alpha strains. Cumulatively, for all 3 strains, viral RNA was detected in 90 of 168 surfaces and 6 of 49 air samples (mean cycle threshold [Ct]=35.2±2.5). No infective virus was identified. No significant differences in prevalence were found between strains.